Determining the Contribution Percentage of Special Physical Fitness Elements to Some Basic Skills of Zakho Club Football Players - Mohammed, Safad Mudhafar (Universitas Nusantara PGRI Kediri, 2024)
This study aimed to identify the relationship and contribution percentages between special physical fitness elements (explosive strength, speed strength, speed endurance, strength endurance) and basic football skills (long distance shooting, dribbling, long pass, heading) in advanced players at Zakho Sports Club. The sample consisted of 15 players who were tested on the fitness elements and skills. The results showed significant correlations between explosive strength and shooting/heading skills; speed strength and dribbling; and strength endurance and heading. Explosive strength had the highest contribution to shooting (48%) and heading (43%). Speed strength contributed most to dribbling (76%). Strength endurance contributed highly to heading (30%). The findings can help guide training efforts and program design for optimal development of key football skills.